Study on resistivity-stress-damage coupling patterns and mechanisms in coal failure under loading - SUN Kang; LIU Qiang; QIU Liming; LI Zhenlei; WANG Chaojie; SUN Qian; LIU Hairui; WANG Litao (Gong-kuang zidonghua)
The occurrence of dynamic disasters is closely related to stress concentration in coal and rock, and coal resistivity varies significantly under different stress states. TTo analyze resistivity variations and damage of coal sample failure under loading, a resistivity loading testing system for coals is developed. Correlation and damage analyses between resistivity and stress at different stages were conducted, leading to the following results: ① the relationship between coal resistivity and stress in coal and rock varied at different stages. Resistivity continuously decreased during the compression stage. The rate of resistivity variation slowed down during the elastic and plastic stages, and it increased sharply during the failure stage. ② The correlation between stress and resistivity exceeded 0.6 during the compression, elastic, and plastic stages, indicating strong correlations. However, during the failure stage, the correlation between stress and resistivity was less than 0.4. ③ The rate of resistivity variation during the entire loading process was divided into two phases: a steady phase with minimal fluctuations and an abrupt phase with a sharp increase in resistivity variation during the failure stage. ④ Before the plastic stage, resistivity was determined by the intrinsic conductivity of the coal matrix. During the plastic and failure stages, resistivity was influenced by pore expansion, permeability, and fracture damage.